Biodiversity of Coleoptera and other invertebrates in urban gardens: a case study in a New Zealand city. Issue 5 (6th March 2015) - Barratt, Barbara I. P.; Dickinson, Katherine J. M.; Freeman, Claire; Porter, Stephan; Johnstone, Peter D.; Wing, Janine; van Heezik, Yolanda; Leather, Simon R.
Abstract Invertebrate biodiversity was investigated in 55 domestic gardens in the city of Dunedin in southern New Zealand. The influence of habitat types within the gardens (lawns, open beds, and closed canopy beds) on invertebrate community structure was investigated by pitfall trapping. Species richness of Coleoptera, the proportion of native species, and effects of pesticide use by householders was examined. The most abundantly trapped taxa were Collembola, Amphipoda, and Diptera. Most taxa were represented in all three habitat types, but Collembola, Diptera, and Araneae were most frequently collected in lawns and Isopoda in open beds. The use of pesticides had no effect on total trap catch, but detritivore numbers were higher in gardens where no insecticide had been used. Opiliones and Acarina were captured in greater numbers in gardens where herbicides had not been used. Over 1400 Coleoptera were identified to 164 species/morphospecies. Species richness averaged 12 species per garden. Staphylinidae, Curculionidae, and Carabidae were the most abundantly collected Coleoptera, both for species and individuals. Species richness was not affected by vegetation type. The coleopteran fauna was predominantly native (80–90%) for species and individuals. The capture of a new to New Zealand weevil species (Exomias pellicidus (Boheman)) suggests that urban studies could play a role in alerting authorities to biosecurity incursions. The study stimulated considerable interest in invertebrates from householders, which might help fill the gap between acquiring environmental awareness and encouraging changes in behaviour towards support for native biodiversity.